Analysis Of Marketing Mix And Development Strategy Of Decorative Plant Business In Cv Minaqu Indonesia - Rahmawati, Febi; Yoesdiarti, Arti; Masithoh, Siti (JURNAL AGRIBISAINS, 2025)
The purpose of this research is to determine the marketing mix of CV Minaqu Indonesia in consumer perception, identify internal factors (strengths and weaknesses) and external factors (opportunities and threats) that influence the company, and determine appropriate alternative strategies to implement in developing the ornamental plant business at CV Minaqu Indonesia . Data analysis uses descriptive and business development strategies. Marketing mix respondents were selected using purposive sampling by the company, and business development strategies were also carried out using purposive sampling, namely expert judgment. The number of marketing mix respondents were 14 CV Minaqu Indonesia consumers and the number of business development strategy respondents was 4 people from CV Minaqu Indonesia parties. Consumer perception of the marketing mix with the lowest percentage is the place factor with an average score of 72.6% and the lowest score variable is 68%, namely ease of location access and distance affordability. The highest percentage is in the process factor with an average score of 84.2% and the highest score variable is 89%, namely the ease of paying online. The IFE matrix score was 3.095 and the EFE matrix was 2.774. The appropriate strategy to use is based on the company's position (in cell IV-grow/develop), namely intensive and integrative strategies, based on the SWOT matrix there are 7 alternative options. As a company that aims to increase sales, CV Minaqu Indonesia should maximize the development of the domestic market and explore further regarding digital creative marketing so that it can continue to adapt to the development of the digital era in marketing strategies.